2013
DOI: 10.1039/c2nr31660a
|View full text |Cite
|
Sign up to set email alerts
|

TiO2nanotube (T_NT) surface treatment revisited: Implications of ZnO, TiCl4, and H2O2treatment on the photoelectrochemical properties of T_NT and T_NT–CdSe

Abstract: The surface treatment of an anodized TiO(2) nanotube (T_NT) is very desirable for enhancing its photoelectrochemical properties and often is a prerequisite to deposition of any overlying layer for photoactivity efficiency improvement. This study provides a comparative analysis of the effects of such surface treatments and the mechanistic insights behind the observed improvements in the performance of the treated T_NTs. T_NT surface treatment using three approaches, viz., TiCl(4), Zn(NH(3))(4)(2+), and H(2)O(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
1
35
0
1
Order By: Relevance
“…Hossain and co-workers [222] investigated T-NTA-CdSe nanocomposite based material by decorating the nanotubes with bubble like CdSe nanoclusters by chemical bath deposition technique. Other methods to simultaneously synthesize and attach CdSe onto T-NTA include the common successive ionic layer absorption and reaction (SILAR) method [223] as well a solvothermal deposition [224]. Coupling CdS with CdSe in tandem on T-NTA has also been investigated [225] and showed the CdS/CdSe couple had the highest performance over CdS or CdSe alone on T-NTA.…”
Section: Catalyst Modificationmentioning
confidence: 99%
“…Hossain and co-workers [222] investigated T-NTA-CdSe nanocomposite based material by decorating the nanotubes with bubble like CdSe nanoclusters by chemical bath deposition technique. Other methods to simultaneously synthesize and attach CdSe onto T-NTA include the common successive ionic layer absorption and reaction (SILAR) method [223] as well a solvothermal deposition [224]. Coupling CdS with CdSe in tandem on T-NTA has also been investigated [225] and showed the CdS/CdSe couple had the highest performance over CdS or CdSe alone on T-NTA.…”
Section: Catalyst Modificationmentioning
confidence: 99%
“…Recent studies have demonstrated the photovoltage decay experiment as a useful method to determine the presence of surface trap states for photoanode materials 40,41. (b) Chronoamperometric I-t curve for TiO 2 -TBU collected at 1.23 V vs. RHE under white light illumination.…”
mentioning
confidence: 99%
“…Unlike mesoporous TiO 2 supports, ordered nanostructures, such as high aspect ratio selforganized TiO 2 nanotube layers [8][9][10] or epitaxially grown TiO 2 nanorods 11,12 , offer the advantage of directed charge transport and controlled phase separation between donor and acceptor parts of the solar cell and thus they seem very promising for nanoscale solar hybrid technologies 9 . Recently, non-silicon solar cells based on TiO 2 nanotube layers sensitized by organic dyes 8 , perovskites 13 and chalcogenides [14][15][16][17] have been presented. The latter class of materials is comparably more stable under UV light and ambient conditions, which make these materials promising for future generation of solar cell devices.…”
Section: Introductionmentioning
confidence: 99%